ANALISIS KARAKTERISTIK PERANG SEMESTA PADA PERTEMPURAN SURABAYA 1945 - La Ode M Hasyim; Ruslan Arief (Sekolah Tinggi Pariwisata Mataram, 2021)
The Battle of Surabaya, which culminated in November 10, 1945, was one of the most important battles in the efforts of the Indonesian people to defend their independence. The universal war based on the persistence, fighting spirit, and courageous mentality of the Indonesian people in Surabaya managed to beat back the British soldiers who were accompanied by NICA, who in fact possessed the equipment, technology and resources far beyond the Indonesian people. Therefore, in this study an analysis of the characteristics of the universal war which became the strategy of the Indonesian people in the Battle of Surabaya was carried out. This research uses qualitative methods and literature study. This research shows that the universal war at that time was synonymous with guerrilla warfare. Some of the prominent characteristics are, the conduct of war is universal, the existence of national intention and national commitment, focuses on the people and is guerrilla, avoids open warfare, there are journalists and media to carry out propaganda and counter-propaganda as well as disseminate information and become agents of spies, and have central figures. So it can be concluded that the success of the Indonesian people in winning the Battle of Surabaya which was marked by the withdrawal of the British from Surabaya was the result of the persistence and efforts of all Indonesian people who were in Surabaya regardless of position, religion, race, age, and ethnicity. With one common goal, and with a high commitment and fighting spirit to escape the shackles of colonialism, the universal war waged in the Battle of Surabaya was successful.